Pupuk Cair Pengurai Sampah Organik di Desa Ciledug Tengah: Liquid Fertilizer to Decompose Organic Waste in Central Ciledug Village - Wigati, Yustina; Rajjiyah, Putri Salma; Hikmah, Ananda Mutiara Nur; Fajriah, Siti Aulia; Anjani, Irna Dini; Sa’adah, Putri; Al Umi, Sindi Oktavia; Nurhayati, Nurhayati; Sumiyati, Mimin; Widayanti, Ari; Kunaedi, Aan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Waste is still a big problem in Indonesia, including Central Ciledug Village, Cirebon. The pile of waste will increase every year if it does not experience the processing and management process of the landfill with an improper system, in addition to the lack of public awareness that makes waste will continue to increase. By dividing organic and inorganic waste, organic waste management is not too difficult because organic waste is easily decomposed. An environmentally friendly solution that can be done to reduce organic waste is to make POC. Liquid Organic Fertilizer (POC) is a type of fertilizer made from leftovers from vegetables and fruits that have decayed and is used to provide organic matter to improve the chemical and biological properties of the soil. The method used is counseling & workshops. The implementation began with the observation of the environment of Central Ciledug Village, the distribution of activity flyers 4 days before the activity, and implementation on Wednesday, August 7, 2024 at 16.00–15.00; located at the Central Ciledug Village Hall, with the participation of Kuwu women, students, PKK women, and Aisyiyah women. The results of the evaluation of pre-test activities showed that 84% of the participants did not know the use of household organic waste. After the post-test increased to 90% understanding of POC. The well-fermented POC produces a pungent aroma of the tape. With counseling activities, it is hoped that it can increase residents' awareness of waste, and the government's synergy efforts in waste control with all parties.